Funcionamiento cognitivo en la vejez y la dependencia en las personas adultas mayores que asisten al proyecto “Abriendo Caminos” del Sector El Salto de la ciudad de Babahoyo - Varela Coloma, Washington Ney (2024)
Cognitive functioning is a mental faculty of the human being, through which the individual can relate to the surrounding environment, by means of sensory organs such as hearing, touch, vision and taste. It is important to highlight that cognitive functions are constituted or divided by 2 types of functions, among which are the basic functions (attention, perception and memory) and complex functions (abstract thoughts, executive activities, among others). On the other hand, dependence refers to the need, help or support that a person needs when he/she is in a vulnerable situation, i.e. because he/she has lost or lacks physical, mental or intellectual autonomy. There are different types of dependence, among which are: physical dependence, emotional dependence, economic dependence, psychological dependence and independence. All these types of dependence generate a negative impact on the physical, psychological and social development of older adults, establishing that old age is a stage in which the individual is vulnerable to contracting diseases. Thus, from the above described, the interest was born to determine the influence of the cognitive functions of old age in the dependence of older adults, for this in the first instance the basic and higher cognitive functions of older adults were evaluated by applying the mini mental test, on the other hand, the degree of dependence of older adults was also evaluated using the Barthel scale, the emotional dependence questionnaire CDE and Brody's scale. These measurement instruments for data collection were applied to 50 adults who attend the project Abriendo Camino. This study was carried out by means of a descriptive research, in which it was concluded that cognitive functions have an influence on the dependence of older adults.